2020
DOI: 10.1109/tpel.2020.2988638
|View full text |Cite
|
Sign up to set email alerts
|

Impact on ZVS Operation by Splitting Inductance to Both Sides of Transformer for 1-MHz GaN Based DAB Converter

Abstract: Zero-voltage-switching (ZVS) of dual active bridge (DAB) converter and its range extension have been studied intensively. However, this paper proves that the external inductance location, i.e. placing on which side of the transformer, does affect the ZVS operation due to transformers' parasitic capacitances, in particular at a high switching frequency of higher than 1 MHz. Thus, this paper, for the first time, gives the mathematical model of the resonant transition during the dead time and thereby analyzes par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…The converter topologies such as LLC resonant, dual active bridge (DAB) and phase shift full bridge (PSFB) are widely used in EV applications. [96][97][98] However, there are several critical issues while designing these converters. The DAB converter can achieve the wide output voltage range and inherent reactive current generation.…”
Section: Dc-dc Convertermentioning
confidence: 99%
“…The converter topologies such as LLC resonant, dual active bridge (DAB) and phase shift full bridge (PSFB) are widely used in EV applications. [96][97][98] However, there are several critical issues while designing these converters. The DAB converter can achieve the wide output voltage range and inherent reactive current generation.…”
Section: Dc-dc Convertermentioning
confidence: 99%
“…Throughout theoretical analysis and simulations in [2], it is revealed that the existence of Cp1 and Cp2 leads to a nonsinusoidal switching-node voltage Vac1. The increase of the high-voltage side external inductance Le1 forms a quasisinusoidal Vac1 which further reduces the minimum dead time to achieve ZVS.…”
Section: Zvs Of High Frequency Dab Convertermentioning
confidence: 99%
“…When selecting the dead time Td to be 6 ns, Le1 should be between 2 µH and 18.4 µH while Le2 is within 100 nH and 1.125 µH to ensure the ZVS. The detailed calculation process can be found in [2].…”
Section: Zvs Of High Frequency Dab Convertermentioning
confidence: 99%
See 2 more Smart Citations